Non-intrusive Energy Harvesting from Vibration of Air Conditioning Condenser Unit Utilizing Piezoelectric Sensors - Yang, Chuan Choong; Rohimi, Rafiq Imran; Mohamad Hanif, Noor Hazrin Hany; Ibrahim, Siti Noorjannah (IEEE, 2021)
One of the renewable energies which is potential to be harvested by end users is from harvesting vibration energy. Vibration energy is generated because of operations and movement of machines, equipment, and tools. Vibration in air-conditioning operation is a widespread problem which various researchers have research on. In this work the vibration generated from the air conditioning condenser unit are harvested utilizing piezoelectric in a non-intrusive manner in such a way that the energy are harvested without interruption to the existing air conditioning operation. Piezoelectric sensor is commonly exploited to convert ambient vibration into electricity. Measurements to identify the location to mount the piezoelectric sensors for optimum harvested energy have been performed. The data obtained from the accelerometer and piezoelectric sensors are identical to identify the optimum location to harvest vibration energy. The highest frequency spot located on the condenser unit with 103.97Hz will be the best placement for the piezoelectric sensor to harvest vibration energy. The voltage produced at the best placement is 375.28 mV. The average voltage harvested are at optimum level when the setting of the air conditioning temperature at low temperature and the air conditioning fan speed at high speed.